The effect of mycophenolate mofetil on disease development in the gld.apoE (-/-) mouse model of accelerated atherosclerosis and systemic lupus erythematosus. - Christophe Richez; Rocco J Richards; Pierre Duffau; Zachary Weitzner; Christopher D Andry; Ian R Rifkin; Tamar Aprahamian (PLoS ONE, 2013)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that is characterized by autoantibody production and inflammatory disease involving multiple organs. Premature atherosclerosis is a common complication of SLE and results in substantial morbidity and mortality from cardiovascular disease (CVD). The reasons for the premature atherosclerosis in SLE are incompletely understood, although chronic inflammation is thought to play an important role. There is currently no known preventative treatment of premature atherosclerosis in SLE. Mycophenolate mofetil (MMF) is an immunosuppressive agent that is commonly used for treatment of patients with SLE. In order to study the impact of this drug on murine lupus disease including premature atherosclerosis development, we treated gld.apoE(-/-) mice, a model of SLE and accelerated atherosclerosis, with MMF. We maintained seven-week old gld.apoE(-/-) mice on a high cholesterol Western diet with or without MMF. After 12 weeks on diet, mice receiving MMF showed decreased atherosclerotic lesion area compared to the control group. MMF treatment also improved the lupus phenotype, indicated by a significant decrease circulating autoantibody levels and ameliorating lupus nephritis associated with this model. This data suggests that the effects of MMF on the immune system may not only be beneficial for lupus, but also for inflammation driving lupus-associated atherosclerosis.